Pigment composition of photosynthetic lightharvesting complexes of eukaryotic alga Emiliania huxle - Troppmair, Nina Nicole (Jihočeská univerzita, 2018)
Pigment composition of light-harvesting complexes from eukaryotic alga Emiliania huxleyi was analysed. Light-harvesting proteins were purified by sucrose gradient ultracentrifugation and ion exchange chromatography. Pigment content was analysed by HPLC. Effect of different growth light intensity on pigment composition was investigated.
Pigment composition of photosynthetic lightharvesting complexes of eukaryotic alga Emiliania huxle